Trends in diabetes-related complications in Hong Kong, 2001–2016: a retrospective cohort study - Hongjiang Wu (Cardiovascular Diabetology, 2020)
Abstract Background Nationwide studies on contemporary trends in incidence of diabetes-related complications in Asia are lacking. We describe trends in incident coronary heart disease (CHD), stroke, heart failure, hyperglycaemic crisis, and lower-extremity amputation (LEA) in people with diabetes in Hong Kong between 2001 and 2016. Methods The Hong Kong Diabetes Surveillance Database (HKDSD) is a territory-wide diabetes cohort identified from Hong Kong Hospital Authority electronic medical record system. We identified events of CHD, stroke, heart failure and hyperglycaemic crisis using hospital principal diagnosis codes at discharge and that of LEA using inpatient procedure codes. We used Joinpoint regression analysis to describe incidence trends by age and sex. Results Between 2001 and 2016, a total of 390,071 men and 380,007 women aged 20 years or older with diabetes were included in the HKDSD. Event rates of CHD, stroke, heart failure, hyperglycaemic crisis and LEA declined by 69.4% (average annual percent change: − 7.6, 95% CI − 10.2, − 5.0), 70.3% (− 8.7, 95% CI − 9.8, − 7.5), 63.6% (− 6.4, 95% CI − 8.0, − 4.7), 59.1% (− 6.6, 95% CI − 12.4, − 0.44), and 67.5% (− 5.8, 95% CI − 7.2, − 4.4), in men and by 77.5% (− 9.9, 95% CI − 11.8, − 7.9), 74.5% (− 9.0, 95% CI − 9.6, − 8.4), 65.8% (− 7.0, 95% CI − 8.0, − 6.0), 81.7% (− 8.5, 95% CI − 10.5, − 6.5), and 72.7% (− 9.1. 95% CI − 12.2, − 5.8) in women, respectively, over a 16-year period in people with diabetes in Hong Kong. Joinpoint analysis identified greater declines in event rates of the five diabetes-related complications in the earlier one-third of study period and slowed down but remained significant until 2016. Event rates decreased for all age groups above 45 years for both sexes. There was no significant change in event rates in the group aged 20–44 years except for decline in hyperglycaemic crisis. Conclusions The event rates of diabetes-related complications have declined substantially with no evidence of stabilization or increase in Hong Kong up to 2016. Improvements in outcome were observed for all age subgroups but not in young people with diabetes, calling for urgent action to improve quality of care to prevent complications in young people at risk.